Dampak Relativisme, Idealisme, Dan Cinta Uang Terhadap Persepsi Etis Penghindaran Pajak - Romario Romario; Basuki Toto Rahmanto (Jurnal Proaksi, 2023)
There are assumptions and perceptions that the taxes paid are not managed properly, giving rise to the assumption that tax avoidance behavior is ethical and reasonable to do. This research was conducted to analyze whether relativism, idealism and love of money influence the ethical perception of tax avoidance. This study uses the theory of planning behavior and the scale of money ethics and ethical perceptions related to tax avoidance. The research population is accounting students from universities in Jakarta. The technique of determining the sample using non-probability sampling obtained 168 respondents. The analytical method used is multiple linear regression analysis and t test to test the hypothesis. The results of the study show that the relativism variable influences the ethical perception of tax avoidance. Idealism and love of money have no effect on ethical perceptions of tax avoidance.